2008
DOI: 10.1177/0363546508314410
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Contact Area and Pressure after Medial Patellofemoral Ligament Reconstruction

Abstract: In medial patellofemoral ligament reconstruction, patellofemoral contact area and pressure may not be adversely affected by use of the nonisometric femoral attachment point used in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 24 publications
2
57
1
1
Order By: Relevance
“…Elias and Cosgarea [28] suggested that a too proximal femoral tunnel positioning might overload the medial patellofemoral compartment thus leading to early osteoarthritis and/or graft rupture. However, according to Melegari et al [29], a non-anatomical tunnel positioning has no impact on the patellofemoral contact area and pressure. Femoral fixation was performed using an absorbable interference screw placed into a blinded tunnel as described by Fithian et al [1] and Schöttle et al [16].…”
Section: Femoral Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…Elias and Cosgarea [28] suggested that a too proximal femoral tunnel positioning might overload the medial patellofemoral compartment thus leading to early osteoarthritis and/or graft rupture. However, according to Melegari et al [29], a non-anatomical tunnel positioning has no impact on the patellofemoral contact area and pressure. Femoral fixation was performed using an absorbable interference screw placed into a blinded tunnel as described by Fithian et al [1] and Schöttle et al [16].…”
Section: Femoral Fixationmentioning
confidence: 99%
“…The graft was tensioned to 10 N at 30°of knee flexion according to the biomechanical findings of Amis et al [4], Beck et al [30] and Melegari et al [29]. According to these authors, graft over-tensioning (N10 N) will lead to overcorrection of the patellar spatial parameters (patellar tilt, patellar translation, etc.)…”
Section: Determination Of Graft Tensionmentioning
confidence: 99%
“…In general, it is thought that a non-anatomical graft tends to over-constrain the patellofemoral (PF) joint. 1,[20][21][22] Theoretically, this pressure results in the loss of knee motion and increases PF osteoarthritis (OA). 1,20 Conversely, in a biomechanical laboratory study using cadaver knees, a non-anatomical femoral attachment point in the adductor tubercle did not alter the pressures on the PF joint in comparison with an anatomical attachment.…”
Section: 413-15mentioning
confidence: 99%
“…1,20 Conversely, in a biomechanical laboratory study using cadaver knees, a non-anatomical femoral attachment point in the adductor tubercle did not alter the pressures on the PF joint in comparison with an anatomical attachment. 21 Then again, controversy persists relative to defining the optimal attachment points for the MPFL graft.…”
Section: 413-15mentioning
confidence: 99%
“…The grafts used for reconstructing this ligament have ranged from synthetic grafts to grafts from the semitendinosus, gracilis and quadriceps tendons and the patellar ligament (2,9,13,(16)(17)(18)(19)(20)(21)(22)(23) . Since the start of the 21 st century, biomechanical studies on cadavers have been developed using simulators constructed for analysis on the patellofemoral joint (7,17,21,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) . These studies can be divided into anatomical and biomechanical.…”
Section: The Authors Declare That There Was No Conflict Of Interest Imentioning
confidence: 99%